Peran Media Pembelajaran dalam Meningkatkan Pemahaman Siswa pada Mata Pelajaran Pendidikan Agama Islam di Sekolah Dasar - Badrus Shalih; Indryyani Claudia; Vella Fitri Aulia; Nur Azizah (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2025)
Instructional media play a crucial role in enhancing the effectiveness of learning, particularly in the subject of Islamic Religious Education (IRE). However, the use of instructional media in elementary schools remains suboptimal, which impacts students’ understanding. This study aims to analyze the role of instructional media in improving students’ understanding of the IRE subject at SDN 03 Banjar Seminai. This study employs a descriptive qualitative approach. The research subjects consisted of PAI teachers, students, and the school principal. Data collection techniques included observation, interviews, and documentation. Data were analyzed using an interactive model comprising data reduction, data presentation, and conclusion drawing, and were validated through source and method triangulation. The results of the study indicate that the use of learning media has been implemented, although it is still limited to simple media. Learning media plays a role in improving students’ understanding by increasing their interest and active participation in learning. Additionally, there are supporting and inhibiting factors: the availability of media and teachers’ willingness serve as supports, while limitations in facilities, time, and skills act as inhibitors. Overall, learning media plays a crucial role in enhancing students’ understanding; therefore, the development of media and the improvement of teachers’ competencies are necessary to optimize the learning process.